Reimagining the Future Public Service Workforce - Dickinson, Helen; Needham, Catherine; Mangan, Catherine; Sullivan, Helen; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book investigates the professional needs and training requirements of an ever-changing public service workforce in Australia and the United Kingdom. It explores the nature of future roles, the types of skills and competencies that will be required and how organisations might recruit, train and develop public servants for these roles. Leading international research - practitioners make recommendations for how local organisations can equip future public servants with the skills and professional capacities for these shifting professional demands, and the skillsets they will require. Drawing on ideas that have been developed in the Australian and UK context, the book delves into the major themes involved in re-imagining the public service workforce and the various forms of capacities and capabilities that this entails. It then explores delivery of this future vision, and its implications in terms of development, recruitment and strategy.
Part 1: Setting the Scene -- Chapter 1. Introduction: imagining the future public service workforce -- Part 2: Major themes in reimagining the public service workforce -- Chapter 2. Boundary Challenges and the work of boundary spanners -- Chapter 3. Supporting Capacities of Public Servants Facing Emotional Labor Demands -- Chapter 4. Narratives and Storytelling -- Chapter 5. Design matters: the implications of design thinking and practice for future public service workforce skills and culture -- Chapter 6. More rave than waltz - why the complexity of public service means the end for hero leadership -- Chapter 7. Empathy, Ethics and Efficiency: 21st century capabilities for public managers -- Part 3: Developing the future public service workforce -- Chapter 8. Developing and recruiting the future public servant -- Chapter 9. Creating a diverse workforce -- Chapter 10. Conclusions.
Keywords: Social policy; Industrial sociology; Public health; Political science; Political sociology; Social Policy; Sociology of Work; Public Health; Political Science; Political Sociology